2004
DOI: 10.1002/ejlt.200300896
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the composition of acyl lipids and triacylglycerol molecular species of pumpkin seeds (Cucurbita spp.) following microwave treatment

Abstract: Variations in the composition of acyl lipids and triacylglycerol molecular species of pumpkin seeds (Cucurbita spp.) following microwave treatmentWhole pumpkin seeds (Cucurbita spp.) of two cultivars were exposed to microwaves for 6, 12, 20 or 30 min at a frequency of 2450 MHz. The kernels were separated from the whole seeds, and were investigated not only for the different acyl lipids and their fatty acid compositions, but also for the molecular species of triacylglycerols (TAGs). A modified argentation TLC p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Dietary EFA includes LA, an n-6 FA, and alpha-linolenic acid (ALA), an n-3 FA. LA and ALA cannot be synthesized by the human organism being necessary to supply them through foods in diet intake [18][19][20]. More importantly, EFA are metabolized with very long chains (VLC) PUFAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary EFA includes LA, an n-6 FA, and alpha-linolenic acid (ALA), an n-3 FA. LA and ALA cannot be synthesized by the human organism being necessary to supply them through foods in diet intake [18][19][20]. More importantly, EFA are metabolized with very long chains (VLC) PUFAs.…”
Section: Discussionmentioning
confidence: 99%
“…The spectrum of precursor ions produced in the ionization of the mass apparatus was compared with similar spectrums available in the three different databases of the Library NIST14. L. Eight majority peaks were identified with their associated retention time: C16:0 with a retention time of 19 (Fig. 2).…”
Section: Figurementioning
confidence: 99%
“…Has been reported that fatty acid linoleic, oleic, palmitic and stearic acids are fatty acids predominant in Cucurbitaceae [20]. Bernardo-Gil et al, 2004, reported a content of 14.7% oleic acid and 61.0% of linoleic acid (omega 6) in pumpkin seeds of C. ficifolia [21] while that Yu et al, 2004, reported 35.0% of oleic acid and 52.0% of linoleic acid (omega 6) from C. ficifolia [22]. In other pumpkin seed, it reported the same situation, for example, Applequist et al, 2006, reported in Fig.…”
Section: Discussionmentioning
confidence: 99%